Gaya Kepemimpinan Dalam Membentuk Kepercayaan Dan Loyalitas Karyawan Coffee Shop Majuma 575 - Alfian Tiko Supangat; Mukarromatul Fitriah; Sukaesih Intan Nuraini; Amilia Fateha; Nurul Setianingrum (GLOBAL SCIENTS PUBLISHER, 2025)
This community service aims to build employee trust and loyalty at Majuma 575 Coffee Shop as an effort to improve the quality of service in the local community. The topic selection was motivated by the need for an effective leadership model in the food and beverage service small and medium enterprise sector that contributes to community economic empowerment. The service method uses a participatory qualitative approach through in-depth interviews, participatory observation, and focus group discussions with owners and employees. The results show that the integration of transformational, participative and bureaucratic leadership styles has succeeded in increasing employees' sense of trust, job satisfaction and affective loyalty through the implementation of SOPs, reward systems and regular discussion forums. This success emphasizes the importance of empowering human resources in developing community businesses and supporting the sustainability of outlet operations.